Job satisfaction and employees turnover: a case of higher educational institutions in Afghanistan / Mahboob Ullah - Ullah, Mahboob (UiTM Cawangan Johor, 2019)
The present study is to determine the influence of Job satisfaction on employees' turnover intentions in the Higher Educational Institutions in Afghanistan. Job satisfaction was measured with remuneration, job security and supervisor role. The data were collected from 315 employees working in Higher Educational Institutions in Afghanistan. The reliability of the data was confirmed through Cronbach' alpha. The hypotheses were examined through regression analysis in SPSS. The findings revealed that job satisfaction has a negative and significant impact on employees' turnover intentions. Additionally, the individual aspect of job satisfaction and turnover intentions was tested. It was found that remuneration, job security and supervisor role have a negative and significant impact on employees' intentions to quit. The study has contributed theoretically through a new conceptual model with unique combination. Practically this study would be useful for the management to find ways to retain skillful employees and sustain competitive advantage.